Upaya Meningkatan Pemahaman Masyarakat Desa Tanjung Mas Mengenai Sistem Akad (Mudharabah) Bagi Hasil Pada Petani Padi - Nabilah Sapirah; Yulia Juwita; Puja; Peny Cahaya Azwari (INDO PUBLISHING, 2025)
The Community Service Program (KKN) in the form of this research is based on the collaboration of KKN Students of Raden Fatah State Islamic University of Palembang in Tanjung Mas Village, Rantau Alai District, Ogan Ilir Regency, South Sumatra Province. This article was created to find out how the people of Tanjung Mas Village carry out the Mudharabah Agreement which they apply in the agricultural system there. The research method used is descriptive qualitative, the way to collect data is by means of Observation, Interviews, and Documentation in the Field. In Islam, agriculture is not seen only as a worldly activity, but is an activity that has spiritual meaning. This can be seen from the assumption that the agricultural products that are utilized have a value of alms, which shows a relationship between activities that are suitable for planting and faith in Allah. The majority of Indonesian people themselves work as farmers, in order to meet their living needs. The results of the study show that the current agricultural management system has developed rapidly, therefore the researcher aims for the people of Tanjung Mas Village to know how the management system in using the correct Mudharabah Agreement is in accordance with Islamic law, in order to support economic development there.